A performance comparison of transformer-less grid tied PV system using diode clamped and neutral point shorted inverters - Suroso Suroso; Hari Siswantoro (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Grid tied photovoltaic (PV) system is an operation mode of PV system working together with utility power supply to provide power to the power load. Conventionally, transformer is used together with the power inverter. The power transformer works as galvanic insolation amongst PV system and power grid. It works also to raise the voltage of power inverter. However, use of transformer will add system complexity, price, weight and size of the entire system. Transformer-less system is an alternative to make the system simpler and more practical in use. The paper discusses performance of transformer-less grid tied PV systems using diode clamped and neutral point shorted inverters. Effects of transformer elimination to the feat of the grid tied PV system especially harmonics content and leakage current of PV system were examined and analyzed. The performance was also compared with the traditional system using H-bridge inverter. The leakage currents did not flow in the system applying diode clamped inverter, and neutral point shorted inverter. In case of harmonics content, the diode clamped inverter injected less harmonics components than the neutral point shorted inverter. The neutral point shorted provides a simpler inverter circuit in the transformerless systems.